Synthesis of Sn-doped Li-rich NMC as a cathode material for Li-ion batteries - Yalcin, Ali; Demir, Muslum; Guler, Mehmet Oguz; Gonen, Mehmet; Akgun, Mesut (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Lithium-rich layered oxide is recognized as a prospective cathode material for next-generation batteries as it has a high theoretical specific capacity. They, however, suffer from voltage decay, and capacity fading upon a long cycling process. Herein, we reported a one-pot approach for preparing Sn-doped Li1.20Mn0.52-xSnxNi0.20Co0.08O2 cathode materials through a supercritical-CO2-assisted method. As-prepared Sn-doped Li-rich NMC presents a well crystalline hexagonal layered structure and polyhedral morphology. The optimal Li-NMC-Sn05 cathode delivers a discharge capacity as high as 250.2 mAh.g- 1 compared with that of 235.1 mAh g-1 at C/20 for the pristine Li-NMC sample. Moreover, the Li-NMC-Sn05 cathode presents enhanced rate-capability performance than the pristine sample at relatively low rates. In addition, the Li-NMC-Sn05 demonstrates excellent energy retention of 93.17%, which is notably higher than that of the pristine Li-NMC (86.4%) after 120 cycles at the C/3 rate. The enhanced capacity, rate capability and cyclic performance of the Li-NMC-Sn05 cathode are attributed to the better interface and structural stability as well as reduced ohmic resistance.
Keywords: Li-rich NMC; Cathode materials; Lithium-ion Batteries; Sn doping; Supercritical-CO 2; assisted; ENHANCED ELECTROCHEMICAL PERFORMANCE; HIGH-CAPACITY; CYCLING STABILITY; LITHIUM; OXIDE; AL; Electrochemistry